2004
DOI: 10.1073/pnas.0402508101
|View full text |Cite
|
Sign up to set email alerts
|

Placental-specific insulin-like growth factor 2 ( Igf2 ) regulates the diffusional exchange characteristics of the mouse placenta

Abstract: Restricted fetal growth is associated with postnatal mortality and morbidity and may be directly related to alterations in the capacity of the placenta to supply nutrients. We proposed previously that imprinted genes can regulate nutrient supply by the placenta. Here, we tested the hypothesis that the insulin-like growth factor 2 gene (Igf2) transcribed from the placental-specific promoter (P0) regulates the development of the diffusional permeability properties of the mouse placenta. Using mice in which place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
218
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(229 citation statements)
references
References 25 publications
9
218
1
1
Order By: Relevance
“…Unlike p57 Kip2 or PHLDA2, IGF-II plays an important role in trophoblast proliferation, invasion and migration [48e50], as well as in cell overgrowth conditions such as BeckwitheWiedemann Syndrome or Wilm's tumor [12,51,52]. Consistent with these findings, IGF-II stimulates the development of the diffusional permeability capacity of murine placenta [53]. We found that hypoxia exerts a divergent influence on the expression of PHLDA2, p57…”
Section: Discussionsupporting
confidence: 76%
“…Unlike p57 Kip2 or PHLDA2, IGF-II plays an important role in trophoblast proliferation, invasion and migration [48e50], as well as in cell overgrowth conditions such as BeckwitheWiedemann Syndrome or Wilm's tumor [12,51,52]. Consistent with these findings, IGF-II stimulates the development of the diffusional permeability capacity of murine placenta [53]. We found that hypoxia exerts a divergent influence on the expression of PHLDA2, p57…”
Section: Discussionsupporting
confidence: 76%
“…In addition, one of the major benefits of transportermediated exchange is that under adverse conditions the rate can be modulated by altering the number of proteins inserted into the plasma membrane [26]. Thus, if the surface area for exchange is reduced experimentally in mice, or the mother is subjected to undernutrition, placental expression of certain amino acid transporters is increased, enhancing the flux [27,28]. Full details of the signalling pathways involved are not available at present, although experimental data implicate placental Igf2 [29].…”
Section: Placental Transportmentioning
confidence: 99%
“…Although a reduced net flux might result from a number of factors, such as poor maternal nutrition, and therefore reduced maternal plasma concentration of specific solutes, the major cause of FGR in the developed world is placental insufficiency (7). It is now clear that all of the factors that determine the capacity of the placenta to transfer nutrients, including blood flow, exchange of barrier structure, and the activity of specific nutrient transporters, may be abnormal in FGR (8)(9)(10)(11)(12)(13)(14)(15)(16). Recent data suggest (reviewed in ref.…”
mentioning
confidence: 99%